Implementasi Urban Farming di Pesantren sebagai Model Edukasi Lingkungan dan Ketahanan Pangan Islami - Asman, Yunita; Anida, Anida; Haikal, T. M.; Zikri, Farhan (Abdimas Indonesian Journal, 2025)
The implementation of urban farming in Islamic boarding schools (pesantren) is an innovative strategy for integrating environmental education, food security, and Islamic values. This activity was carried out at an Islamic boarding school in Bireuen Regency, utilizing unproductive land to grow various crops such as vegetables and melons with seeds and seeds. The main objective of this program is to increase the food self-sufficiency of the Islamic boarding school while also shaping the character of the students through practical-based learning and Islamic ecotheological values. The implementation method involves participatory observation, technical assistance, and direct involvement of students in all stages, from soil cultivation, planting, maintenance, and harvesting. The results show an increase in land productivity and food efficiency, with the Islamic boarding school able to meet up to 20% of its internal food needs. Furthermore, this activity fosters ecological awareness, discipline, and responsibility in the students towards the environment. Conceptually, this practice aligns with eco-pesantren theory and the concept of khalifah fil ardh, which emphasizes the role of humans in maintaining the balance of nature. Thus, urban farming has proven effective not only as a solution for food security but also as a model for sustainable character and spiritual education in the Islamic boarding school environment.